2014
DOI: 10.1353/jda.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Fiscal Redistribution, and Governmental Corruption: Evidence from Chinese Provincial Data

Abstract: We build a theoretical model that describes the relationship between income inequality, fiscal redistribution and corruption in China. With between-group econometric model, using the provincial panel data of China from 1997 to 2006, this paper finds strong evidence in support of the propositions revealed by the theoretical model. The conclusion of empirical analysis is that fiscal redistribution as a remedy of the failure of market allocation fails to restrain income inequality. In contrast, it worsens income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…De Freitas’ (2012) study showed that countries with an informal sector which has high income will rely heavily on consumption tax to redistribute. Mi and Liu (2014) took the analysis further by incorporating governmental corruption in the fight to close the income inequality gap through fiscal redistribution. Mi and Liu (2014) concluded that fiscal redistribution worsens income inequality due to corruption in the implementation of fiscal redistribution policies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…De Freitas’ (2012) study showed that countries with an informal sector which has high income will rely heavily on consumption tax to redistribute. Mi and Liu (2014) took the analysis further by incorporating governmental corruption in the fight to close the income inequality gap through fiscal redistribution. Mi and Liu (2014) concluded that fiscal redistribution worsens income inequality due to corruption in the implementation of fiscal redistribution policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mi and Liu (2014) took the analysis further by incorporating governmental corruption in the fight to close the income inequality gap through fiscal redistribution. Mi and Liu (2014) concluded that fiscal redistribution worsens income inequality due to corruption in the implementation of fiscal redistribution policies. Hu and Liu (2009) study showed that in rural areas, the redistributive effect of tax is not obvious but in urban areas, individual income tax has a strong adverse effect on income inequality.…”
Section: Ijdi 223mentioning
confidence: 99%